Antifouling properties of copper oxide microparticles and zinc oxide nanoparticles in greenhouse cooling systems - Al-Busaidi, Azhar; Al-Mamari, Rahma; Kyaw, Htet Htet; Myint, Myo Tay Zar; Al-Abri, Mohammed; Dobretsov, Sergey (Frontiers in Nanotechnology, 2025)
Biofouling in the cooling systems of greenhouses in arid climates is a major problem. The current study describes the usage of coatings composed of copper oxide microparticles (CuO MPs) and zinc oxide nanoparticles (ZnO NPs) in greenhouse cooling systems for biofouling protection. A simple spray coating method was employed to coat cooling cardboard with the CuO MPs and ZnO NPs. Biofouling properties of coated cardboard were investigated as antimicrobial activities in laboratory experiments under light and dark conditions using different types of Gram-positive and Gram-negative bacteria isolated from the greenhouse. CuO MPs coating showed the strongest antimicrobial activity compared to ZnO NPs in Gram-positive bacteria (Bacillus infantis) under both conditions. Almost the same antimicrobial activity was observed for CuO MPs and ZnO NPs with Gram-negative (Escherichia coli) bacteria. Furthermore, the antialgal activity of the coatings was investigated against Scenedesmus sp. and Pinnularia sp. isolated from the greenhouse. Results demonstrated that CuO MPs exhibited the strongest antialgal activity. The observed antifouling activity was mainly due to the production of reactive oxygen species (ROS) and ions from ZnO NPs and CuO MPs coatings. The results of this study suggest that CuO MPs coatings can be applicable for antifouling protection of greenhouse cooling systems.